2011
DOI: 10.1007/s11033-011-1376-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-based treatment for cartilage defects in osteoarthritis

Abstract: Osteoarthritis (OA) is a common disorder and the restoration of the diseased articular cartilage in patients with OA is still a challenge for researchers and clinicians. Currently, a variety of experimental strategies have investigated whether mesenchymal stem cells (MSCs) instead of chondrocytes can be used for the regeneration and maintenance of articular cartilage in OA. MSCs can modulate the immune response of individuals and positively influence the microenvironment of the stem cells already present in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 56 publications
0
75
0
Order By: Relevance
“…In surgically induced OA in sheep, intra-articular injection of MSCs, with and without prechondrogenic differentiation, retarded OA progression and showed improved cartilage organization and quality [15]. Other models including mice [16] and rabbits [17] also showed encouraging results of postponing OA progression [18]. Recently, a few clinical studies transplanting MSCs into human OA knees have reported formation of hyaline-like cartilage and Aim: Mesenchymal stem cell (MSC)-based therapy presents a promising approach for treating osteoarthritis (OA).…”
Section: Bidirectional and Mutually Beneficial Interactions Between Hmentioning
confidence: 99%
“…In surgically induced OA in sheep, intra-articular injection of MSCs, with and without prechondrogenic differentiation, retarded OA progression and showed improved cartilage organization and quality [15]. Other models including mice [16] and rabbits [17] also showed encouraging results of postponing OA progression [18]. Recently, a few clinical studies transplanting MSCs into human OA knees have reported formation of hyaline-like cartilage and Aim: Mesenchymal stem cell (MSC)-based therapy presents a promising approach for treating osteoarthritis (OA).…”
Section: Bidirectional and Mutually Beneficial Interactions Between Hmentioning
confidence: 99%
“…Moreover, pain reduction that results from the action of injected cells occurs after a certain period of time, but not immediately. In contrast, the application of steroids provides significant and immediate pain reduction, but this effect wanes after a relatively short time, two to three weeks (Coleman et al, 2010;Qui et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This provides, at least at medium-term data, remission of pain and swelling, with good functional recovery and the ability to resume previous work activity, as compared to the ACT technique, with the advantage of a single operative step and a significant cost reduction [8,[16][17][18][19][20][21][22][23][24].…”
Section: The Paracrine Effect and The Exosome Nanoworldmentioning
confidence: 99%